2022
DOI: 10.3390/plants11212942
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Tolerance in Casuarina glauca: Insights from the Branchlets Transcriptome

Abstract: Climate change and the accelerated rate of population growth are imposing a progressive degradation of natural ecosystems worldwide. In this context, the use of pioneer trees represents a powerful approach to reverse the situation. Among others, N2-fixing actinorhizal trees constitute important elements of plant communities and have been successfully used in land reclamation at a global scale. In this study, we have analyzed the transcriptome of the photosynthetic organs of Casuarina glauca (branchlets) to unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Many studies of plants have shown that ABA-and JAmediated signal transduction pathways are related to the response to drought stress [38][39][40]. It has been reported that the ABA and JA signaling pathways of C. equisetifolia and Casuarina glauca were activated under salt stress [41,42]. ABA that accumulates under drought stress can activate specific serine / threonine kinase family SnRK2, which can phosphorylate downstream transcription factors and activate ABA response genes [43,44].…”
Section: Plant Hormone Signal Transduction Pathways In Response To Dr...mentioning
confidence: 99%
“…Many studies of plants have shown that ABA-and JAmediated signal transduction pathways are related to the response to drought stress [38][39][40]. It has been reported that the ABA and JA signaling pathways of C. equisetifolia and Casuarina glauca were activated under salt stress [41,42]. ABA that accumulates under drought stress can activate specific serine / threonine kinase family SnRK2, which can phosphorylate downstream transcription factors and activate ABA response genes [43,44].…”
Section: Plant Hormone Signal Transduction Pathways In Response To Dr...mentioning
confidence: 99%
“…In response to high salinity, salt-tolerant species elevate antioxidant levels to balance ROS, coordinating cellular processes such as water uptake and ion regulation [6,[9][10][11]. However, most plants are not tolerant to salinity, and a high degree of responses can even Agronomy 2023, 13, 3076 2 of 12 be found among sensitive and tolerant species.…”
Section: Introductionmentioning
confidence: 99%